Trichoderma bombaxalis sp. nov., isolated from rhizosphere soils of Lycium barbarum - Yu, Shuang; Wang, Rui; Liu, Hong-Wei; Zhang, Xue; Sun, Jing-Zu (Phytotaxa, 2022)
Trichoderma bombaxalis isolated from rhizosphere soils of five-year-old Lycium barbarum is described as a novel species. A combined approach is used to characterize T. bombaxalis including cultural and microscopic features, and phylogenetic analyses of the cascaded dataset of internal transcribed spacer (ITS) regions, RNA polymerase II subunit (RPB2), and the translation elongation factor 1-α gene (TEF1-α). The phylogeny reveals that T. bombaxalis belongs to section Hypocreanum, and is closely related to T. austriacum, T. eucorticoides, T. sulphureum, T. subsulphureum and T. victoriense, but represents a novel taxon. These fungi are characterized by often producing verticillium-like conidiophores and ellipsoidal conidia. Distinctions between the new species and its close relatives are compared and discussed. The ability of T. bombaxalis to degrade cellulose and hemicellulose is also estimated.